1999
DOI: 10.1063/1.479530
|View full text |Cite
|
Sign up to set email alerts
|

Rotational state-to-state rate constants and pressure broadening coefficients for He–C2H2 collisions: Theory and experiment

Abstract: Converged close-coupling and coupled-states calculations were used to obtain state-to-state rate constants and pressure broadening coefficients for the collisional rotational (de-)excitation of C2H2 by He. The ab initio potential used in these calculations was previously computed by symmetry-adapted perturbation theory. The computed pressure broadening coefficients and total rate constants agree well with the available experimental data. In the experimental part of the paper stimulated Raman-pumping has been u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 35 publications
3
25
0
Order By: Relevance
“…[78][79][80], but no resolved infrared or microwave spectrum has yet been reported, except very recently for C 2 D 2 -He [81]. Our attempts to observe the related 2CH spectrum using FANTASIOþ have all failed, so far.…”
Section: Neon and Heliummentioning
confidence: 99%
“…[78][79][80], but no resolved infrared or microwave spectrum has yet been reported, except very recently for C 2 D 2 -He [81]. Our attempts to observe the related 2CH spectrum using FANTASIOþ have all failed, so far.…”
Section: Neon and Heliummentioning
confidence: 99%
“…For some other systems, such Ne-CO (Moszynski et al 1997) or Ne-C 2 H 2 (Bemish et al 1998), small scalings were necessary to quantitatively reproduce the experimental data. At the same time, it was shown that the ab initio potentials reproduce the (scarce) data for the state-to-state cross sections and rate constants; see, for instance, Heijmen et al (1997a) and Heijmen et al (1999a), respectively. Over the past decade, the complexity of the systems that can be treated by ab initio methods has A50, page 4 of 14 increased dramatically; see for instance, Bukowski et al (2007) and Jankowski et al (2012), who show the accuracy that can be reached for systems like the water dimer or CO-H 2 .…”
Section: Methodologies For Collisions With Heavy Particlesmentioning
confidence: 92%
“…We observed a series of rotational resonances at low scattering energies, below 20 cm À1 with a sharp one observed at energy lower than 2 cm À1 . Such resonances are known to result from Feshbach resonances when the total energy becomes equal to the energy of a quasi-bound level of the complex [4]. From the sharpness of the peak, one can conclude that the rotationally predissociative state is quite long lived.…”
Section: Outline Of Dynamical Calculationsmentioning
confidence: 94%
“…The exchange-deformation energy was computed directly from the supermolecule Hartree-Fock interaction energy. The computational scheme for the pair interactions was the same as in our previous works (see, for instance, [4]). The SAPT interaction energies were always computed with the dimer basis set.…”
Section: Outline Of Sapt Calculationsmentioning
confidence: 99%
See 1 more Smart Citation